Genetic diversity of Dipterocarpus costatus in the lowland tropical forests of Tan Phu, Dong Nai province - Tam, Nguyen Minh; Viet Thanh, Tran Thi; Duy, Vu Dinh; Anh Tuan, Nguyen Le; The, Truong Huu; Don, Pham Quy; Duc, Nguyen Minh (Academia Journal of Biology, 2015)
Dipterocarpus costatus (Dipterocarpaceae) is narrowly distributed in lowland rainforests in southern Vietnam. Due to overexploitation and habitat destruction during 1980 and 1990 years, this species is now threatened. For species conservation in tropical forests, genetic diversity was investigated on the basis of nine microsatellite (single sequence repeat, SSR). In all, 31 D. costatus individuals in Tan Phu rainforests were analyzed in this study. Eight loci were polymorphic. A total of 22 alelles were observed across the studied loci. The polymorphic information content (PIC) averaged 0.142 (0.055-0.222) and indicated low polymorphic value. Other values including discrimination power (PD = 0.288), resolving power (Rp = 2.192) and Marker index (MI = 0.099) were revealed. The SSR data indicated a low genetic diversity (A = 1.9; Ho = 0.108 and He = 0.124) and the inbreeding value was high, Fis = 0.137. The dendrogram grouping the individuals by unweighted pair-group method with arithmetic averages method revealed two main clusters. All individuals in a cluster were related with closed geographic distances. This study also indicated the importance of conserving the genetic resources of Dipterocarpus costatus species in Tan Phu rainforests